Vapor−Solid Growth of One-Dimensional Layer-Structured Gallium Sulfide Nanostructures - Shen, Guozhen; Chen, Di; Chen, Po-Chiang; Zhou, Chongwu (ACS nano, 2009)
Gallium sulfide (GaS) is a wide direct bandgap semiconductor with uniform layered structure used in photoelectric devices, electrical sensors, and nonlinear optical applications. We report here the controlled synthesis of various high-quality one-dimensional GaS nanostructures (thin nanowires, nanobelts, and zigzag nanobelts) as well as other kinds of GaS products (microbelts, hexagonal microplates, and GaS/Ga2O3 heterostructured nanobelts) via a simple vapor−solid method. The morphology and structures of the products can be easily controlled by substrate temperature and evaporation source. Optical properties of GaS thin nanowires and nanobelts were investigated and both show an emission band centered at 580 nm.